Preparation method of nanoscale lithium titanium aluminum phosphate solid electrolyte

By controlling the reaction temperature and pH of the solid electrolyte precursor of titanium aluminum phosphate and using a low-temperature heat treatment process, nano-scale products are directly synthesized, which solves the problems of long process, high energy consumption and uneven particle size in the existing processes, and achieves precise control and energy consumption reduction.

CN119612478APending Publication Date: 2025-03-14CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411843186.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing preparation process of titanium aluminum lithium lithium phosphate solid electrolytes has problems such as long process flow, high energy consumption, long production cycle, uneven particle size, wide particle size distribution, and limited particle size level control.

Method used

By controlling the reaction temperature and pH value in the reaction of precursor 1, and combining with a low-temperature heat treatment process, nano-scale titanium aluminum lithium phosphate solid electrolyte is directly synthesized to avoid subsequent grinding and crushing processes.

Benefits of technology

It realizes precise control of the product particle size, shortens the process flow and production cycle, reduces energy consumption, and improves the particle size uniformity and chemical stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612478A_ABST
    Figure CN119612478A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nanoscale lithium aluminum titanium phosphate solid electrolyte, which comprises the following steps: mixing a phosphorus source and a titanium source by using a liquid phase method to react, obtaining a precursor 1 after the reaction is completed under the conditions that the reaction temperature is 25-180 DEG C and the pH value of a reaction system is 0-2, then adding a lithium source and an aluminum source, and preparing a precursor 2 by using a liquid phase reaction, and finally, washing and drying, and carrying out heat treatment to prepare the nano-scale lithium aluminum titanium phosphate solid electrolyte. According to the method, the reaction temperature and the pH value of a reaction system in the process of preparing the precursor 1 are controlled, so that the particle size level of the product is controlled, the introduction of a rear-end crushing process is avoided, the technological process is shortened, and the production period is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte. Background Art

[0002] Lithium titanium aluminum phosphate solid electrolytes are increasingly widely used due to their high ionic conductivity and high chemical stability. Different application scenarios have different requirements for the particle size level of lithium titanium aluminum phosphate solid electrolytes. The mainstream products on the market currently include micron-level, submicron-level, and nano-level lithium titanium aluminum phosphates, all of which are prepared by post-processing the finished products using traditional dry grinding and wet grinding processes. This process route has the problems of long process flow, high energy consumption, long production cycle, uneven particle size, wide particle size distribution, and limited particle size level control. Summary of the invention

[0003] In order to overcome the problems in the prior art, the present invention provides a method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte. By controlling the reaction temperature and the pH of the reaction system during the preparation of the precursor 1, the nano-scale lithium titanium aluminum phosphate solid electrolyte is directly synthesized in combination with a low-temperature heat treatment process, thereby avoiding the subsequent grinding and crushing process.

[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is: The present invention provides a method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte, comprising the following steps: S1. Mix a phosphorus source and a titanium source by a liquid phase method, the reaction temperature is 25-180° C., the pH of the reaction system is 0-2, and after the reaction is completed, the precursor 1 is prepared by washing and drying.

[0005] S2. Add lithium source and aluminum source to precursor 1, and prepare precursor 2 by liquid phase reaction at a temperature of 45-120°C.

[0006] S3, washing and drying the precursor 2 and then heat treating it to prepare a nano-scale lithium aluminum titanium phosphate solid electrolyte.

[0007] In the present invention, a phosphorus source and a titanium source are first mixed in liquid phase, and a liquid phase crystallization reaction occurs under an acidic pH of 0-2. The liquid phase reaction system is controlled at 25-180° C. A portion of the titanium source is hydrolyzed under strong acidic conditions to produce titanium ions and a phosphorus source to generate titanium hydrogen phosphate and a hydrate thereof, and a portion of the titanium source forms a coating layer on the surface of the precipitated new phase, and finally titanium monohydrogen phosphate (Ti(HPO4)2) coated with a titanium-containing compound or a hydrate of titanium monohydrogen phosphate coated with a titanium-containing compound is obtained, and then a lithium source and an aluminum source are added to further react in liquid phase. The temperature is controlled at 45-120°C, and the lithium ions in the lithium source and the aluminum ions in the aluminum source exchange protons with the titanium monohydrogen phosphate (Ti(HPO4)2) coated with the titanium-containing compound, or the hydrogen ions in the lattice of the titanium monohydrogen phosphate hydrate coated with the titanium-containing compound to obtain a precursor 2, which is then washed and dried and heat-treated, and sintered at low temperature to obtain a nano-scale lithium aluminum titanium phosphate solid electrolyte. By controlling the pH and temperature of the reaction of the precursor 1, ultrafine nano-sized lithium aluminum titanium phosphate is prepared and precise control of the particle size of the product is achieved.

[0008] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the pH of the reaction system is 0-1.

[0009] In the present invention, a strong acidic reaction system is used to ensure the conversion rate and purity of the precursor 1 product.

[0010] As an optional embodiment, in the preparation method provided by the present invention, in step S1, after the reaction is completed, deionized water is used for washing, and the pH of the washed product is 4-7.

[0011] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the precursor 1 is titanium monohydrogen phosphate coated with a titanium-containing compound or titanium monohydrogen phosphate hydrate coated with a titanium-containing compound, and the particle size of the precursor 1 is 0.02μm-1.5μm; the molar ratio of the titanium element in the titanium-containing compound to the titanium element in the titanium monohydrogen phosphate is 0.10-0.32.

[0012] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the reaction method of the phosphorus source and the titanium source is selected from one of high-energy ball milling reaction, high-temperature and high-pressure hydrothermal reaction, coprecipitation reaction, condensation reflux reaction or aging reaction.

[0013] In the present invention, the precursor 1 can be obtained in different particle size ranges through different reaction methods. For example, the particle size of the precursor 1 obtained by high-energy ball milling reaction is above 100nm, that by high-temperature and high-pressure hydrothermal reaction is above 500nm, that by coprecipitation reaction is 0.01-2μm, that by condensation reflux reaction is above 500nm, and that by aging reaction is 0.02-300nm.

[0014] As an optional embodiment, in the preparation method provided by the present invention, the molar ratio of phosphorus element to titanium element in the phosphorus source and the titanium source is ≥1.5.

[0015] As an optional embodiment, in the preparation method provided by the present invention, in step S2, the temperature of the liquid phase reaction is 60-120° C., and the stirring linear speed during the liquid phase reaction is >3.5 m / s.

[0016] In the present invention, the speed of liquid phase reaction is controlled, a certain stirring intensity is ensured, the diffusion process is accelerated, the reaction uniformity is ensured, the precipitated crystal nuclei are ensured to be uniform, and at the same time it is beneficial to control the generation rate of crystal nuclei and avoid the reaction from continuing to grow on the generated crystal nuclei.

[0017] As an optional embodiment, in the preparation method provided by the present invention, in step S2, the molar ratio of the titanium element in the precursor 1 to the lithium element in the lithium source is 0.01-1.72:1, and the molar ratio of the titanium element in the precursor 1 to the aluminum element in the aluminum source is 0.1-2:1.

[0018] As an optional embodiment, in the preparation method provided by the present invention, in step S3, the temperature of the heat treatment is 450-800°C.

[0019] In the present invention, the lattice and surface ions are rearranged during the heat treatment process to form a new crystal structure, so that the precursor becomes lithium aluminum titanium phosphate crystals. Controlling within the above temperature range is conducive to forming the best product. If the temperature is too low, the reaction cannot occur, and if the reaction is too high, it will decompose and produce impurities, and at the same time, the crystals will further melt and grow, and finally become large particles of the product.

[0020] As an optional embodiment, in the preparation method provided by the present invention, the phosphorus source is selected from one or more of P2O5, H3PO4, NH4H2PO4, (NH4)2HPO4 and H4P2O7.

[0021] As an optional embodiment, in the preparation method provided by the invention, the titanium source is selected from TiO2, H2TiO3, Ti(SO4)2, TiCl4, TiOSO4, TiO(OH)2, C 16 H 36 One or more of O4Ti and Ti(OCH(CH3)2)4.

[0022] As an optional embodiment, in the preparation method provided by the present invention, the lithium source is selected from one or more of LiBr, LiNO3, Li2SO4, Li2C2O4, LiCl, CH3COOLi and LiH2PO4.

[0023] As an optional embodiment, in the preparation method provided by the present invention, the aluminum source is selected from one or more of AlCl3, Al(NO)3, Al(NO)3·9H2O and Al2(SO4)3.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, a phosphorus source and a titanium source are first reacted by a liquid phase method to prepare a precursor 1, and then a lithium source and an aluminum source are added to the precursor 1 to prepare a precursor 2. By controlling the pH and reaction temperature during the reaction, the particle size level of the product is controlled, thereby avoiding the introduction of a back-end crushing process, shortening the process flow, and reducing the production cycle.

[0025] (2) In the present invention, by controlling the precursor preparation process, the preparation of lithium aluminum titanium phosphate solid electrolytes at the micron, submicron and nanometer levels can be achieved, and the smallest level can reach 20-30nm.

[0026] (3) The present invention adopts a liquid phase synthesis process combined with a low temperature heat treatment process, which has low energy consumption and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a morphology diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 1 of the present invention; Figure 2 This is a morphology diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 2 of the present invention; Figure 3 This is a morphology diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 3 of the present invention; Figure 4 This is a morphology diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 4 of the present invention; Figure 5 This is a morphology diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Comparative Example 1 of the present invention; Figure 6 This is a morphology diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Comparative Example 2 of the present invention; Figure 7 This is the XRD diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 1 of the present invention; Figure 8This is the XRD diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 2 of the present invention; Fig. 9 This is the XRD diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 3 of the present invention; Fig.10 This is the XRD diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Example 4 of the present invention; Fig.11 The XRD pattern of the precursor 1 prepared in Example 3 of the present invention; Fig.12 This is the XRD pattern of the precursor 1 prepared in Comparative Example 2 of the present invention; Fig.13 This is the XRD diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0029] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0030] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0032] Example 1 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 16.21 g TiO2 and 41.29 g H3PO4 (85 wt%) respectively, and the pH of the reaction system is less than 1.

[0033] (2) The weighed raw materials were transferred into a high-energy ball mill and mixed evenly. The mixture was ball milled at normal pressure and 25°C with a ball-to-material ratio of 4:1 and a ball milling speed of 800 rpm / min for 36 hours with an interval of 60 seconds. After the reaction was completed, the mixture was filtered.

[0034] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 5, and then dried to obtain precursor 1.

[0035] (4) Add 5 g of fully dried precursor 1, 250 g of 3 mol / L LiNO3, and 21 g of Al(NO3)3·9H2O, respectively, and react at 120°C for 5 h with a stirring speed of 800 rpm / min to obtain the product.

[0036] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0037] (6) Precursor 2 was heat treated at 550°C for 4 h to prepare the LATP product.

[0038] Example 2 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 80 g of 15% H3PO4 aqueous solution and add an appropriate amount of concentrated sulfuric acid aqueous solution to adjust the pH of the phosphoric acid aqueous solution to 0.8.

[0039] (2) Place the above-mentioned phosphoric acid aqueous solution with pH = 0.8 at 60°C and stir at a stirring speed of 800 rpm / min. Slowly add 5g H2TiO3 and monitor the pH change during the reaction to ensure that the pH of the system is ≤2. Filter after the liquid phase reaction for 3 hours.

[0040] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 5, and then dried to obtain precursor 1.

[0041] (4) Add 5 g of fully dried precursor 1, 96 g of 1 mol / L LiCl, and 35 g of Al(NO3)3·9H2O, respectively, and react at 60°C for 5 h with a stirring speed of 800 rpm / min to obtain the product.

[0042] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0043] (6) Precursor 2 was heat treated at 550°C for 4 h to prepare the LATP product.

[0044] Example 3 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 80 g of 15% H3PO4 aqueous solution and add an appropriate amount of concentrated sulfuric acid aqueous solution to adjust the pH of the phosphoric acid aqueous solution to 0.8.

[0045] (2) Place the above-mentioned phosphoric acid aqueous solution with pH = 0.8 at 80°C and stir at a stirring speed of 1200 rpm / min. Slowly add 29 g of Ti(SO4)2. Monitor the pH change during the reaction to ensure that the pH of the system is ≤ 2. Filter after the liquid phase reaction for 3 hours.

[0046] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 5, and then dried to obtain precursor 1.

[0047] (4) Add 5 g of fully dried precursor 1, 288 g of 3 mol / L LiNO3, and 35 g of Al(NO3)3·9H2O, respectively, and react at 60°C for 5 h with a stirring speed of 800 rpm / min to obtain the product.

[0048] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0049] (6) Precursor 2 was heat treated at 550°C for 4 h to prepare the LATP product.

[0050] Example 4 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 140 g of 10% NH4H2PO4 aqueous solution and add an appropriate amount of concentrated sulfuric acid aqueous solution to adjust the pH of the phosphoric acid aqueous solution to 0.8.

[0051] (2) Place the above-mentioned phosphoric acid aqueous solution with pH = 0.8 under stirring at 160°C and a stirring speed of 1600 rpm / min, slowly add 10 g of TiOSO4, monitor the pH change during the reaction, ensure that the pH of the system is ≤ 2, and filter after the liquid phase reaction for 3 hours.

[0052] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 5, and then dried to obtain precursor 1.

[0053] (4) Add 5 g of fully dried precursor 1, 160 g of 3 mol / L Li2SO4, and 35 g of Al(NO3)3·9H2O, respectively, and react at 60°C for 5 h with a stirring speed of 800 rpm / min to obtain the product.

[0054] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0055] (6) Precursor 2 was heat treated at 800°C for 4 h to prepare the LATP product.

[0056] Example 5 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 80 g of 15% H3PO4 aqueous solution and add an appropriate amount of concentrated sulfuric acid aqueous solution to adjust the pH of the phosphoric acid aqueous solution to 0.8.

[0057] (2) Place the above-mentioned phosphoric acid aqueous solution with pH = 0.8 at 80°C and stir at a stirring speed of 1200 rpm / min. Slowly add 10 g of TiOSO4. Monitor the pH change during the reaction to ensure that the pH of the system is ≤ 2. Filter after the liquid phase reaction for 3 hours.

[0058] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 4, and then dried to obtain precursor 1.

[0059] (4) Add 5 g of fully dried precursor 1, 288 g of 3 mol / L LiNO3, and 35 g of Al(NO3)3·9H2O, respectively, and react at 60°C for 5 h with a stirring speed of 800 rpm / min to obtain the product.

[0060] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0061] (6) Precursor 2 was heat treated at 550°C for 4 h to prepare the LATP product.

[0062] Example 6 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 80 g of 15% H3PO4 aqueous solution and add an appropriate amount of concentrated sulfuric acid aqueous solution to adjust the pH of the phosphoric acid aqueous solution to 0.8.

[0063] (2) The above-mentioned phosphoric acid aqueous solution with pH = 0.8 was placed in a stirred state at 80°C at a stirring speed of 800 rpm / min, and 10 g of TiOSO4 was slowly added. The pH change during the reaction was monitored to ensure that the pH of the system was ≤ 2. The liquid phase reaction was performed for 3 hours and then filtered.

[0064] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 6.5, and then dried to obtain precursor 1.

[0065] (4) Add 5 g of fully dried precursor 1, 288 g of 3 mol / L LiNO3, and 35 g of Al(NO3)3·9H2O, respectively, and react at 60°C for 5 h with a stirring speed of 800 rpm / min to obtain the product.

[0066] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0067] (6) Precursor 2 was heat treated at 550°C for 4 h to prepare the LATP product.

[0068] Example 7 A method for preparing a nano-scale lithium titanium aluminum phosphate solid electrolyte comprises the following steps: (1) Weigh 140 g of 10% NH4H2PO4 aqueous solution and add an appropriate amount of concentrated sulfuric acid aqueous solution to adjust the pH of the phosphoric acid aqueous solution to 0.8.

[0069] (2) The above-mentioned phosphoric acid aqueous solution with pH = 0.8 was placed in a stirred state at 80°C at a stirring speed of 800 rpm / min, and 10 g of TiOSO4 was slowly added. The pH change during the reaction was monitored to ensure that the pH of the system was ≤ 2. The liquid phase reaction was performed for 3 hours and then filtered.

[0070] (3) Deionized water was added to prepare an aqueous solution with a ratio of 10:1, and the deionized water was repeatedly washed until the pH value was 5, and then dried to obtain precursor 1.

[0071] (4) Add 5 g of fully dried precursor 1, 288 g of 3 mol / L LiNO3, and 14.6 g of Al(NO3)3, respectively, react at 60°C for 5 h, and stir at 800 rpm / min to obtain the product.

[0072] (5) The product was filtered, washed, filtered again, and dried at 120 °C for 10 h to obtain precursor 2.

[0073] (6) Precursor 2 was heat treated at 750°C for 4 h to prepare the LATP product.

[0074] Comparative Example 1 The preparation method of nano-scale lithium aluminum titanium phosphate solid electrolyte based on wet grinding comprises the following steps: (1) Weigh 33.67 g Li2CO3, 10.71 g Al2O3, 94.85 g TiO2, 242.2 g NH3H2PO4, and 1525.72 g C3H8O respectively.

[0075] (2) The weighed raw materials were transferred into a high-energy ball mill for mixing at a ball milling speed of 300 rpm / min for 6 h with an interval of 60 s.

[0076] (3) The high-energy ball milling product was transferred into a vacuum drying oven and dried at 120 °C for 10 h to prepare precursor 1.

[0077] (4) The precursor 1 is transferred into a sintering furnace and heat treated at 900°C for 4 hours to prepare a lithium aluminum titanium phosphate product.

[0078] (5) Weigh 500 g of lithium aluminum titanium phosphate product and 1166.7 g of C3H8O respectively, transfer the weighed raw materials into a high-energy ball mill for wet grinding at a ball mill speed of 400 rpm / min and a ball milling time of 10 h.

[0079] (6) The ball-milled slurry was transferred to a sand mill for further wet grinding, using 0.3 mm zirconium beads and a sand milling time of 60 min.

[0080] (7) The sand-ground slurry is transferred to a vacuum drying oven for drying at 120°C for 10 h to finally obtain a nano-scale lithium aluminum titanium phosphate product.

[0081] Comparative Example 2 The difference from Example 3 is that in step (1), the pH is adjusted to 3, and the pH does not need to be monitored during the reaction process. The remaining steps are the same as in Example 3.

[0082] Comparative Example 3 The difference from Example 3 is that in step (3), the mixture is repeatedly washed in deionized water until the temperature reaches 3.5, and the remaining steps are the same as those in Example 3.

[0083] Comparative Example 4 The difference from Example 3 is that the reaction in step (6) is carried out at 900° C., and the remaining steps are the same as those in Example 3.

[0084] The precursor 1 and lithium aluminum titanium phosphate product prepared in the embodiment of the present invention and comparative example 3 were tested, and the results are shown in Table 1.

[0085] Table 1: Element content in lithium aluminum titanium phosphate

[0086] It can be seen from Table 1 that the lithium and aluminum doping amounts in the lithium titanium aluminum phosphate solid electrolyte in the embodiment are generally around 1-2.5%, and the pH of the precursor 1 in Comparative Example 3 is 3.5. The reason is that in the slightly acidic environment, the lattice spacing in the precursor 1 becomes smaller, which is not conducive to proton exchange, resulting in a decrease in the lithium and aluminum doping amounts.

[0087] Figure 1-4The morphology of nano-lithium aluminum titanium phosphate solid electrolyte prepared in Examples 1-4 are respectively, Figure 5 and Figure 6 The morphology diagrams of nano-lithium aluminum titanium phosphate solid electrolytes prepared in Comparative Example 1 and Comparative Example 2 respectively show that a high-purity lithium aluminum titanium phosphate solid electrolyte is successfully prepared based on the preparation method of a nano-lithium aluminum titanium phosphate solid electrolyte of the present invention. The experimental results of Example 1 and Example 2 show that customized preparation of nano-lithium aluminum titanium phosphate solid electrolyte products of different specifications can be achieved by selecting different precursor synthesis paths and controlling the precursor synthesis reaction conditions; Figure 1~Figure 4 It can be seen that by controlling the reaction temperature of the precursor 1, the finished lithium aluminum titanium phosphate product is precisely controlled, and a lithium aluminum titanium phosphate solid electrolyte product with a primary particle size of 0.02μm~1.5μm is prepared within a temperature range of 25~180℃. Compared with the traditional solid-phase method for preparing nano-scale lithium aluminum titanium phosphate in Comparative Example 1, the process is simpler, the particle size is more controllable, and the energy consumption is lower. Figure 3 and Figure 6 It can be seen that by comparing the morphology of the products prepared in Example 3 with that in Comparative Example 2, pH has a significant effect on the particle size of the finished product, the crystallinity of the precursor 1, and the particle size of the product. Based on the same reaction temperature, the crystallinity of the precursor 1 prepared in Example 3 is higher than that in Comparative Example 2, and the physical phase is more complete, so that the primary particles of the obtained lithium aluminum titanium phosphate product are more complete and the primary particles are larger. If the pH of the reaction system is further reduced, the precursor 1 with ion exchange capacity may not be obtained, thereby affecting further reactions. Therefore, this step should be carried out in a strongly acidic reaction system. According to the experimental results of Example 3, Example 5, Example 6 and Comparative Example 3, the content of lithium ions and aluminum atoms in lithium aluminum titanium phosphate is greatly affected by the pH of the precursor 1, and maintaining a neutral pH is more conducive to the occurrence of ion exchange reactions.

[0088] The heat treatment process is a key process for the preparation of solid electrolytes. Since the present invention prepares a product with a small particle size through the preparation of precursor 1, the specific surface area of ​​the reactants is increased, which is beneficial to the ion diffusion during the solid-phase reaction. The lattice doping is combined with the ion exchange process to reduce the solid-phase reaction barrier, thereby achieving low-temperature sintering. Figure 7-Figure 10 The XRD patterns of nano-lithium aluminum titanium phosphate solid electrolytes prepared in Example 1, Example 2, Example 3, and Example 4 of the present invention are shown in FIG. Figure 11-Figure 12 The XRD patterns of the precursor 1 prepared in Example 3 and Comparative Example 2 of the present invention are shown respectively. Fig.13 The XRD diagram of the nano-lithium aluminum titanium phosphate solid electrolyte prepared in Comparative Example 4 of the present invention is shown in FIG. Figure 7-13As shown, comparing Example 3 with Comparative Example 4, the lithium aluminum titanium phosphate product prepared in Comparative Example 4 contains original lithium titanium phosphate and lithium phosphate impurities, indicating that the solid electrolyte decomposes under 900°C. Combined with the heat treatment temperature of Comparative Example 1, it further illustrates that the precursor prepared by the present invention has higher reactivity, and the heat treatment temperature should be controlled within a reasonable range.

[0089] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A method for preparing nano-scale lithium titanium aluminum phosphate solid electrolyte, characterized in that: The following steps are involved: S1, mixing a phosphorus source and a titanium source by a liquid phase method, the reaction temperature is 25-180° C., the pH of the reaction system is 0-2, and after the reaction is completed, washing and drying are performed to prepare a precursor 1; S2, adding a lithium source and an aluminum source to the precursor 1, and preparing the precursor 2 by a liquid phase reaction at a temperature of 45-120°C; S3, washing and drying the precursor 2 and then heat treating it to prepare a nano-scale lithium aluminum titanium phosphate solid electrolyte.

2. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S1, the pH of the reaction system is 0-1.

3. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S1, after the reaction is completed, deionized water is used for washing, and the pH of the washed product is 4-7.

4. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S1, the precursor 1 is titanium monohydrogen phosphate coated with a titanium-containing compound or titanium monohydrogen phosphate hydrate coated with a titanium-containing compound, and the particle size of the precursor 1 is 0.02 μm-1.5 μm; the molar ratio of the titanium element in the titanium-containing compound to the titanium element in the titanium monohydrogen phosphate is 0.1-0.

32.

5. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S1, the reaction method of the phosphorus source and the titanium source is selected from one of high-energy ball milling reaction, high-temperature and high-pressure hydrothermal reaction, coprecipitation reaction, condensation reflux reaction or aging reaction.

6. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: The molar ratio of phosphorus element to titanium element in the phosphorus source and the titanium source is ≥1.

5.

7. The method for preparing the nanoscale lithium titanium aluminum phosphate solid electrolyte according to claim 1, characterized in that: The stirring speed during the liquid phase reaction was ≥800 rpm / min.

8. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S2, the molar ratio of the titanium element in the precursor 1 to the lithium element in the lithium source is 0.01-1.72:1, and the molar ratio of the titanium element in the precursor 1 to the aluminum element in the aluminum source is 0.1-2:

1.

9. The method for preparing nano-scale lithium aluminum titanium phosphate solid electrolyte according to claim 1, characterized in that: In step S3, the heat treatment temperature is 450-800°C.

10. The method for preparing the nano-scale lithium aluminum titanium phosphate solid electrolyte according to any one of claims 1 to 9, characterized in that: The phosphorus source is selected from one or more of P2O5, H3PO4, NH4H2PO4, (NH4)2HPO4 and H4P2O7, and the titanium source is selected from TiO2, H2TiO3, Ti(SO4)2, TiCl4, TiOSO4, TiO(OH)2, C 16 H 36 O4Ti and Ti(OCH(CH3)2)4; the lithium source is selected from one or more of LiBr, LiNO3, Li2SO4, Li2C2O4, LiCl, CH3COOLi and LiH2PO4, and the aluminum source is selected from one or more of AlCl3, Al(NO)3, Al(NO)3·9H2O and Al2(SO4)3.

Citation Information

Cited By

  • Method for preparing lithium titanium phosphate by taking doped titanium pyrophosphate as precursor

    CN119750526A

  • A method for preparing lithium titanium phosphate by using doped titanium pyrophosphate as a precursor

    CN119750526B

  • A kind of ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization and its preparation method

    CN122647140A